The need to (climate) adapt: perceptions of German sports event planners on the imperative to address climate change - Werner, Kim (Frontiers in Sports and Active Living, 2024)
Introduction While the impact of anthropogenic climate change on sports and the subsequent need for adaptation to evolving climatic conditions are acknowledged, there remains a notable paucity of scientific inquiry within the realm of sports and sports event studies specifically addressing climate change and its ramifications for event planning and management. Existing studies predominantly stem from health, medical, weather and climate science and mostly focus on mega-events and elite athlete contexts. Moreover, they often only focus on one specific impact (e.g., extreme heat) without providing a comprehensive summary or overview of all eminent impacts, resulting risks and potential adaptation strategies. This study aims to explore how (German) sports events are impacted by climate change and identify measures for organizers to address these impacts. Methods Following a comprehensive literature review, semi-structured interviews with event planners and organizers in Germany were conducted, ranging from small local events to weekly league competitions to national championships and major events. Results The findings demonstrate that climate change adaptation is not yet a primary focus in the German sports event context. While some planners, especially those of large-scale events, have started implementing adaptation measures, others are only beginning to address the issue. Discussion The study discusses the challenges that sports event organizers face in adjusting to the adverse effects of climate change and also examines specific adaptation strategies. The paper emphasizes the imperative for organizers to incorporate climate adaptation measures more effectively into routine event planning and management processes, and provides practical guidelines to achieve this integration.